PENGARUH EFIKASI DIRI, CARA BELAJAR, PERSEPSI SISWA TENTANG KOMUNIKASI GURU DAN PERSEPSI SISWA TENTANG PERHATIAN ORANGTUA TERHADAP HASIL BELAJAR SISWA KELAS XI MAN DI KOTA PALU - Dewi Sri Wahyuni (MATEMATIKA DAN PEMBELAJARAN, 2016)
This research is motivated by factors that influence students’ learning outcomes, namely internal factors and external factors. This research aims to identify the description and influence of self-efficacy, learning method, students’ perceptions of teachers’ communication and parents’ attention toward students’ learning outcomes of class XI students at MAN in Palu. This research is an ex post facto with causality in nature. The samples of the research were 122 students selected from Class XI at MAN in Palu using a proportional stratified random sampling. The instruments used: (1) self-efficacy scale, (2) learning method scale, (3) the scale of students’ perceptions on teachers’ communication, (4) the scale of students’ perception on parents’ attention, (5) test of mathematics learning outcomes of class XI. Data were analyzed using descriptive statistics and inferential statistics with SEM method (Structural Equation Modeling). The results of the research indicate that: Self efficacy of class XI students at MAN in Palu is in moderate category, which can be interpreted that self efficacy gives good influence to class XI students at MAN in Palu. Students’ perception on teachers’ communication is in very high category, which can be interpreted that the students’ perception on the teachers’ communication gives a very good impact to class XI students at MAN in Palu. Students’ perception on parents’ attention is in low category, which can be interpreted that the perceptions of students’ on parents’ attention has an adverse effect in class XI at MAN in Palu. Learning method of students is in moderate category, and cognitive learning outcomes of students is at a very low category. Key Words: Self-efficacy, learning styles, teacher communication, and parental attention.